VACCINE MANDATES: DEEPENING THE RIFT BETWEEN POLARIZED IDEOLOGY ON SOCIAL MEDIA (Journal of Contemporary Philology, 2022)
Facing the consequences of one of the most deadly waves of the Covid-19 pandemic towards the end of 2021, the political authorities all over the world struggled to persuade people to get as massively vaccinated as possible, using rhetoric which ranged from threats to even begging. Focusing on the vaccine hesitancy by certain populations, most governments have started to impose a vaccine mandate for all citizens, which resulted in eruption of protests across a number of European, Australian and American cities. Consequently, the intolerance of “the other”, either vaccinated or unvaccinated, has risen among social media users. By combining the methods of critical discourse and pragmatic analysis, this research attempts to investigate the main pro and con argumentation of social media users (Macedonian and English) made in the comment threads of posted online news on mandatory vaccination. The detailed discursive analysis of the samples reveals that fear, triggered by threat as well as risk, is what justifies both sides’ attitude and reasoning.
Keywords: vaccine mandate; vaccine hesitancy; CDA; pragmatics; social media